Optimasi Produksi Endokitinase dari Jamur Mikoparasit Trichoderma reesei - Harjono Harjono; Siti Muslimah Widyastuti (Jurnal Perlindungan Tanaman Indonesia, 2001)
The objective of the experiment was to select optimal medium composition to induce endochitinase production of Trichoderma reesei. Growing media were prepared by substitution of 0.5% colloidal chitin, 0.5% colloidal chitin and 1% Polyvinyl Pyrrolidon (PVP), 1% crab shell chitin (Sigma), 1% crab shell chitin and 1% PVP into Richard’sMedium (RM). Selected bioagent T. reesei isolate 13 was grown onto the media and the specific activity of endochitinase was measured. The results showed that T. reesei grown in all media performed enzyme expression. The highest specific activity of endochitinase was detected on T. reesei grown in RM medium substituted with colloidal chitin and PVP, followed by the same fungi in RM medium substituted with crab shell chitin plus PVP, colloidal chitin and crab shell chitin alone.